Fast Long-Range Photon Counting Depth Imaging With Sparse Single-Photon Data - Yan Kang; Lifei Li; Dawei Liu; Dongjian Li; Tongyi Zhang; Wei Zhao (IEEE Photonics Journal)
Fast depth imaging of noncooperative targets at a range of up to 900 m is demonstrated based on the time-of-flight time-correlated single-photon counting technique. Experimental results shown that our image system has the ability of reconstructing depth images with data of less than one photon per pixel. Especially, utilizing a modified total variation regularization algorithm with an optimal initial value, the acquisition time necessary for each pixel could be reduced by a factor of 8 compared to the traditional median filter approach, and the image processing time is extremely improved. This depth imaging system is a low-light-level device for a variety of applications, such as target detection, space surveillance, and distance measurement.